Acute myeloid leukaemia in a patient with Seckel syndrome. Issue 2 (February 1994) - Hayani, A; Suarez, C R; Molnar, Z; LeBeau, M; Godwin, J
Abstract : We report a female patient with Seckel syndrome who developed acute myeloid leukaemia at the age of 26 years. Analysis of bone marrow chromosomes showed an abnormal clone with abnormalities involving multiple chromosomes, including monosomy 7, trisomy 8, trisomy 11, and loss of the long arm of chromosome 5. After treatment with chemotherapy, the patient experienced severe toxicity with profound bone marrow aplasia and died of pneumonia two months later. We suggest that patients with Seckel syndrome may be at risk of developing myelodysplasia and acute myeloid leukaemia. They may also have poor tolerance to cytotoxic therapy.